Factors associated with sex trade involvement among male participants in a prospective study of injection drug users. Issue 6 (30th November 2004) - Kuyper, L M; Lampinen, T M; Li, K; Spittal, P M; Hogg, R S; Schechter, M T; Wood, E
Abstract : Objectives: While much research to date has examined female sex trade work, little has been done to evaluate factors associated with male sex trade involvement or to assess their health service needs. This is particularly true for male sex trade workers who are also injection drug users (IDUs). Therefore, the present analyses were undertaken to evaluate factors associated with sex trade work in a prospective cohort study of male IDUs. Methods: We identified factors associated with sex trade involvement among male participants enrolled in the Vancouver Injection Drug Users Study (VIDUS). Since serial measures for each individual were available at semiannual intervals, variables potentially associated with sex trade involvement were evaluated with adjusted odds ratios (AOR) and 95% confidence intervals (CI) computed using generalised estimating equations (GEE). Results: Between 1996 and 2003, 995 male IDUs were enrolled into the VIDUS cohort among whom 108 (11%) reported being involved in the sex trade at enrolment and 102 (10%) individuals initiated sex trade involvement during the follow up period. In multivariate analyses, factors independently associated with sex trade involvement included HIV positive serostatus (AOR: 1.77 (95% CI: 1.44 to 2.17)), daily cocaine injection (AOR: 1.37 (95% CI: 1.11 to 1.70)), daily crack smoking (AOR: 1.36 (95% CI: 1.07 to 1.72)), borrowing syringes (AOR: 1.73 (95% CI: 1.32 to 2.25)), and inconsistent use of condoms with casual sexual partners (AOR 0.66, CI 0.53 to 0.82). We also found that male sex trade workers were more likely to report having sought but been unable to access substance abuse treatment (AOR: 1.28 (95% CI: 0.98 to 1.67); p = 0.076). Conclusions: Males involved in the sex trade in this setting have higher levels of HIV infection and engage in risky injection behaviours at an elevated rate. Since these behaviours have major implications for HIV acquisition and public health, prevention efforts and targeted provision of addiction treatment to this population should be expanded.